The Problem of Form and Content in Hegel’s Aesthetics - Al-Kharraz, Faisal Bashir ((Faculty of Arts Journal) مجلة كلية الآداب - جامعة مصراتة, 2016)
This study explores Hegel’s aesthetic philosophy, particularly his view that art is a manifestation of the Absolute Spirit, alongside religion and philosophy. It analyzes the dialectical tension between form and content in art, in light of mimesis (imitation) and mythology, while also addressing the broader philosophical oppositions between subjectivity and objectivity, and spirit and matter, within Hegel’s tripartite classification of art: symbolic, classical, and romantic. The importance of this study lies in offering a concise philosophical entry into Hegel’s theory of art history and aesthetics. It highlights the deep interconnection between art, religion, and philosophy as expressions of the Absolute Spirit. The methodology follows a historical-analytical approach, supported by comparative reflections, aiming to provide a fresh and condensed interpretation of Hegelian aesthetics. The research objectives include presenting key aspects of Hegel’s aesthetic philosophy, clarifying his stance on the problem of form versus content, exploring the role of mythology in artistic expression, and analyzing the dialectical unity of art, religion, and philosophy in Hegel’s thought.